Zákon o obchodních korporacích : komentář - Štenglová, Ivana, 1942-; Havel, Bohumil, 1975-; Cileček, Filip, 1973-; Kuhn, Petr, 1975-; Šuk, Petr, 1973- (C.H. Beck, 2017)
Komentované znění zákona o obchodních korporacích.
Keywords: obchodní společnosti -- Česko; corporations -- Czechia; zákony; komentáře; laws; commentaries